A GUIDE TO LOGICAL PLURALISM FOR NON-LOGICIANS. Issue 47 (30th October 2017) - Weber, Zach
Abstract : There exists today an infinite variety (literally) of formal logics, different systems with incompatible properties. One way to explain the existence of many logics is to posit logical pluralism : to suppose that there is in fact more than one correct logic. In this selective guide – designed for non-logicians – we look at some examples of how different logics come into apparent conflict with each other. Then we look at different ways of understanding the idea of logical pluralism. Our question throughout will be a basic one: does logical pluralism have any limits?